As per the question,
wave equation is given as "x=a\\sin(\\omega)t"
Let "dP=\\dfrac{2dt}{T}-------------(i)"
Where T is the time period and dt is the time taken in x to x+dx
"x=a\\sin(\\omega)t"
"dx=a\\omega \\cos(\\omega t)dt"
"\\Rightarrow dt=\\dfrac{dx}{a\\omega \\cos(\\omega t)}"
now
from the equation (i),
"dP=\\dfrac{2dx}{a\\omega\\cos(\\omega t)T}"
we know that "\\omega=\\dfrac{2\\pi}{T}"
"\\Rightarrow dP=\\dfrac{2dx}{a\\dfrac{2\\pi}{T}\\cos(\\omega t)T}=\\dfrac{2dx}{2\\pi a\\cos(\\omega t)}"
now we know that "x=a\\sin(\\omega)t"
"\\sin(\\omega t)=\\dfrac{x}{a}"
"\\cos(\\omega t)=\\sqrt{1-\\sin^2(\\omega t)}"
"\\Rightarrow \\cos(\\omega t)=\\sqrt{1-(\\dfrac{x}{a})^2}"
"\\Rightarrow dP=\\dfrac{2dx}{2\\pi a\\cos(\\omega t)}"
"\\Rightarrow dP=\\dfrac{2dx}{2\\pi a\\sqrt{1-(\\dfrac{x}{a})^2}}"
"\\Rightarrow dP=\\dfrac{dx}{\\pi \\sqrt{a^2-(x)^2}}"
"\\Rightarrow \\dfrac{dP}{dx}=\\dfrac{1}{\\pi \\sqrt{a^2-x^2}}"
Comments
Leave a comment